PERAN GURU DAN ORANGTUA DALAM MENGOPTIMALKAN KEGIATAN PEMBELAJARAN DARING PADA MATA PELAJARAN IPS DI SMP NEGERI 2 MAZINO - Naitolo Faana; Yasozanolo Gaho (Curve Elasticity: Jurnal Pendidikan Ekonomi, 2023)
The implementation of online learning activities certainly has many obstacles starting from the systematic implementation to the availability of supporting facilities for learning activities. This study aims to determine the role of teachers in optimizing online learning activities in SMP Negeri 2 Mazino, the role of parents in optimizing online learning activities in SMP Negeri 2 Mazino, and factors that support/inhibit the role of teachers and parents in SMP Negeri 2 Mazino. Qualitative research method with Case Study approach. Data collection techniques using observation, interviews and documentation. Data analysis techniques use data reduction stage, data presentation, conclusion or verification and final conclusion. The validity of the data uses techniques of reliability, reliability, dependability, and certainty. The subjects of this study were teachers and parents in SMP Negeri 2 Mazino. The results of this study show that the role of teachers SMP Negeri 2 Mazino is to prepare learning devices, using applications that are easy to operate systems such as WhatsApp and Google Classroom. The role of parents in SMP Negeri 2 Mazino is to provide supervision to children only at the beginning of the implementation of online learning activities and provide facilities needed by children during the implementation of online learning activities. Factors that support and inhibit the role of teachers and parents in SMP Negeri 2 Mazino is the existence of a fairly good school management where the principal of SMP Negeri 2 Mazino requires every teacher to send evidence or report after doing online learning while factors that inhibit the role of teachers and parents in the implementation of online learning activities, one of which is poor internet network and not all students have devices in the form of mobile phones needed in the implementation of online learning activities.